THU0096 Effect of anakinra (il-1ra) and soluble tumour necrosis factor receptor i (stnf-ri) on cellular immune function in rats. (1st June 2001) - Atkinson, JE; House, RV; Cranmer, PS; Colucil, AE; Davis, H; Edwards, CK; Miller, DM
Abstract : Background: Objectives: This study investigated the potential for combined treatment with inhibitors of IL-1 and TNF-α to affect immunocompetence by assessing function of selected cell types involved in host resistance. Methods: Basal NK cell activity, lymphoproliferation following stimulation with anti-CD3, pokeweedmitogen or concanavalin A, and antibody forming cell response (AFC) were determined in splenocytes from female rats (F-344; N = 12 per group) treated with placebo, IL-1ra alone (20 or 200 mg/kg, SC daily), sTNF-RI alone (5 or 50 mg/kg, SC twice weekly) or the dose combinations of the two cytokine inhibitors for 21 days. Satellite groups received positive control agents for the NK cell assay (0.5 mL anti-asialo GM 1 antibody) or the mitogenesis and AFC assay (25 mg/kg cyclophosphamide). Results: Basal NK cell response was increased 21% (p < 0.05) over placebo control only at the combination of 200 mg/kg IL-1ra + 5 mg/kg sTNF-RI. No effect was noted with IL-1ra or TNF-RI alone or at higher combination doses. Cells from IL-1ra (200 mg/kg) treated animals showed minimal decreases (30%, p < 0.05) on lymphocyte proliferation only in response to anti CD3-mediated proliferation. Statistically significant differences (+10 to – 48%) in proliferative activity to all mitogens were observed with sTNF-RI alone or in combination with IL1-ra, but were not dose related. Diminution in the AFC response (29–36%) was noted for sTNF-RI alone (50 mg/kg) or in combination with both Il-1ra doses compared to the control group; however the differences were not statistically significant. IL1-ra alone, the low dose of sTNF-RI (5 mg/kg) alone or in combination with IL-1ra doses had no significant effect on AFC response. Conclusion: Thus, IL-1ra alone has minimal effects on selected functions of the immune system. Effects on immune function noted at 50 mg/kg sTNF-RI were considered minimal and importantly were not exacerbated by the combination of IL-1ra.